2021
DOI: 10.1016/s2666-7568(20)30068-4
|View full text |Cite
|
Sign up to set email alerts
|

The potential of rapalogs to enhance resilience against SARS-CoV-2 infection and reduce the severity of COVID-19

Abstract: COVID-19 disproportionately affects older people, with likelihood of severe complications and death mirroring that of other age-associated diseases. Inhibition of the mechanistic target of rapamycin complex 1 (mTORC1) has been shown to delay or reverse many age-related phenotypes, including declining immune function. Rapamycin (sirolimus) and rapamycin derivatives are US Food and Drug Administration-approved inhibitors of mTORC1 with broad clinical utility and well established dosing and safety profiles. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 88 publications
(113 reference statements)
0
40
0
Order By: Relevance
“…It is possible that Rapamycin, as a co-adjuvant treatment, can improve clinical outcome because it is able to block viral interactions that promotes cell growth, and viral replication. Moreover, Rapamycin can reduce pro-inflammatory cytokines decreasing cell damage in patients with severe COVID-19 ( Bischof et al, 2021 ). The metabolic changes conferred by SARS-CoV-2 infection in renal epithelial cells and lung air-fluid interface (ALI) cultures, showed that SARS-CoV-2 infection reduces the oxidative metabolism of glutamine while maintaining reductive carboxylation, increasing the activity of mTORC1.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that Rapamycin, as a co-adjuvant treatment, can improve clinical outcome because it is able to block viral interactions that promotes cell growth, and viral replication. Moreover, Rapamycin can reduce pro-inflammatory cytokines decreasing cell damage in patients with severe COVID-19 ( Bischof et al, 2021 ). The metabolic changes conferred by SARS-CoV-2 infection in renal epithelial cells and lung air-fluid interface (ALI) cultures, showed that SARS-CoV-2 infection reduces the oxidative metabolism of glutamine while maintaining reductive carboxylation, increasing the activity of mTORC1.…”
Section: Discussionmentioning
confidence: 99%
“…There are several active clinical trials registered on ClinicalTrials.gov for mTOR inhibitors, such as the rapamycin analog Sirolinus. These clinical trials are based on the proposed effects of rapamycin on restoring T-cell functionality and decrease cytokine storm [94,95], the direct antiviral effect [96], and in aging-related declining of the immune function [97]. Metformin, a medicine commonly used to treat Type 2 Diabetes and a well-known mTOR inhibitor [98], has been demonstrated to reduce COVID-19 mortality [99].…”
Section: Discussionmentioning
confidence: 99%
“…It is used to prevent organ transplant rejection and treat lung disease [251]. Research has continued on the effectiveness of sirolimus against COVID-19 [252]. Sirolimus' function as an mTOR inhibitor could help to inhibit COVID-19 virus replication [253].…”
Section: Immunosuppressive Compoundsmentioning
confidence: 99%